Birth Cohort Changes in the Subjective Well-Being of Chinese College Students: A Cross-Temporal Meta-Analysis, 2002–2017 - Su, Qian; Liu, Guofang (Frontiers in Psychology, 2020)
Abstract: According to the happiness-income paradox, economic growth within a country does not necessarily lead to an increase in well-being. However, previous literature also showed that economic growth has a greater impact on well-being in a low-income country than a high-income country. China is a typical developing country that has experienced dramatic development in recent decades. How did the well-being of the Chinese change? To examine birth cohort changes in Chinese college students’ subjective well-being, a cross-temporal meta-analysis that involved 100 studies was conducted (106 data points, N = 55, 830). The results showed that Chinese college students’ well-being increased by at least .45 standard deviations from 2002 to 2017. In addition, their subjective well-being was significantly correlated with social indicators (e.g., GDP per capita, divorce rate, and university enrollment rate) for the corresponding years and 3 years prior to the collection of subjective well-being data. It is evident that social changes play an important role in predicting changes in well-being.